Analisis Pemakaian BMHP pada Pasien Persalinan Normal, Operasi Caesar Umum, Dan BPJS di RSUD Sorong - Levina Virginia; Lukman Hardia; Wahyuni Watora (Yayasan Literasi Sains Indonesia, 2025)
Disposable Medical Materials play an important role in maternity services and their use is influenced by the type of delivery and the patient's payment method. This study aims to analyze the influence of both on the use of disposable medical materials in the Emergency Department Pharmacy and the Medical Depot of Dr. J.P. Wanane Regional General Hospital, Sorong Regency, and to comparing the use of disposable medical materials between caesarean section patients of the social security administration and general normal delivery. This quantitative cross-sectional study used a total sampling of 108 delivery patients from January 2025 to June 2025. Data were analyzed using the Kruskal-Wallis and Mann-Whitney tests (α=5%). The Kruskal-Wallis test results showed a significant difference in the use of medical consumables between patient groups based on the combination of delivery type and payment method (p = 0.011). Caesarean section patients from the Social Security Administration used the most medical consumables, while patients with normal delivery used the least. Mann-Whitney analysis confirmed that the use of medical consumables was higher among Caesarean section patients from the Social Security Administration compared to normal delivery (p = 0.007). Thus, the type of delivery and payment method had a significant influence, with the highest use of medical consumables among Caesarean section patients from the Social Security Administration. It was concluded that the type of delivery and payment method had a significant effect, with the highest use of disposable medical materials in the social security administration caesarean section patients.